Urgensi Tes Kesehatan Suntik Tt (Tetanus Toksoid) Bagi Calon Pengantin Perempuan Perspektif Maqashid Al-Syariah: (Studi Kasus Di Kecamatan Jambesari Darus Sholah Bondowoso) - Fatmawati Fatmawati (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2020)
The development of modern times can affect several factors including health. Even in choosing a partner, you must really know the condition of your partner. The practice that is developing in the District of Jambesari Darus Sholah is injecting TT (Tetanus Toxoid). However, in reality, not all prospective brides carry out TT injections. Therefore, how is the practice of implementing TT injections for prospective brides in the District of Jambesari darus Sholah Bondowoso and to what extent is it important or urgent that TT injections (Tetanus Toxoid) are carried out.This research method uses a type of field research (Field Research). Collecting data using observation techniques, interviews and documentation. By utilizing midwives/nurses, KUA and prospective/bride brides as subjects to provide information related to TT injections in Jambesari Darus Sholah District.Based on the results of the study, it can be concluded that the practice of implementing TT injections is not done by all prospective brides due to several factors: not knowing the importance of TT injections, no advice from KUA and any party, and fear of injections. The urgency of injecting TT from the perspective of Maqashid Syariah can be seen from the concepts of لَاضَرَرَوَلَاضِرَارَand saad ad-dzari'ah with these two concepts supporting kulliyatul khamsa which in this case emphasizes more on hifdz nafs and hifdz nasl. In this case, it can minimize death in mother and child.